Musterbildungen. Ein alternativer Zugang zur Fernsehgeschichte: Über Lynn Spigels TV Snapshots – An Archive of Everyday Life - Miggelbrink, Monique (Cargo H. 56)

The DaimlerChrysler takeover failure revisited from a varieties-of-capitalism perspective - Riach, John Rankin Wood; Schneider, Martin (Cross Cultural and Strategic Management)
Purpose The purpose of this paper is to revisit the disastrous DaimlerChrysler AG takeover episode from 1998 to 2007 in order to arrive at a more comprehensive explanation of this and other merger and takeover failures based on institutional theory. Design/methodology/approach The case study is based on various secondary sources of information and on the insights that one of the authors gained from working for 14 years in various positions for Daimler-Benz and DaimlerChrysler. Findings DaimlerChrysler failed because top management made mistakes in trying to globalize the company. They were unable to realize possible synergies between the two companies, which brought complementary resources into the merger. Furthermore, they did not account for the institutional embeddedness of strategies when they adopted lean production globally, diffused the production system developed in Germany to other parts of the world and tried to implement a global stock enlisted in New York and Frankfurt. The underlying theoretical framework is relevant for other merger and acquisition cases. It features institutional embeddedness, path dependency and institutional arbitrage. Originality/value The paper develops an institutional perspective on DaimlerChrysler and on cross-border merger and acquisition failure more generally. The perspective is organized around the varieties-of-capitalism approach. This contribution is important because there is increasing dissatisfaction with the dominant explanation of cross-border merger and acquisition failure, which is based on the allegedly failed management of culture “clashes.”
Keywords: Organizational Behavior and Human Resource Management; Strategy and Management; Sociology and Political Science; Cultural Studies; Business and International Management

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Gall, François Le (Proceedings of the 54th ACM Symposium on Theory of Computing (STOC))
The Quantum Singular Value Transformation (QSVT) is a recent technique that gives a unified framework to describe most quantum algorithms discovered so far, and may lead to the development of novel quantum algorithms. In this paper we investigate the hardness of classically simulating the QSVT. A recent result by Chia, Gily\'en, Li, Lin, Tang and Wang (STOC 2020) showed that the QSVT can be efficiently "dequantized" for low-rank matrices, and discussed its implication to quantum machine learning. In this work, motivated by establishing the superiority of quantum algorithms for quantum chemistry and making progress on the quantum PCP conjecture, we focus on the other main class of matrices considered in applications of the QSVT, sparse matrices. We first show how to efficiently "dequantize", with arbitrarily small constant precision, the QSVT associated with a low-degree polynomial. We apply this technique to design classical algorithms that estimate, with constant precision, the singular values of a sparse matrix. We show in particular that a central computational problem considered by quantum algorithms for quantum chemistry (estimating the ground state energy of a local Hamiltonian when given, as an additional input, a state sufficiently close to the ground state) can be solved efficiently with constant precision on a classical computer. As a complementary result, we prove that with inverse-polynomial precision, the same problem becomes BQP-complete. This gives theoretical evidence for the superiority of quantum algorithms for chemistry, and strongly suggests that said superiority stems from the improved precision achievable in the quantum setting. We also discuss how this dequantization technique may help make progress on the central quantum PCP conjecture.

Ich. Das bin ich! Zugehörigkeit, Freundschaft und Familie. Zyklus 2 - Tenberge, Claudia; von Braunmühl, Susanne

Lebensformen, Welt, Gesellschaft. Alltagsleben, Gemeinschaft und Feste. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Ich und die anderen. Zugehörigkeit, Freundschaft und Familie. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Kultur und Kommunikation. Religion, Sprache und Verständigung. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Große Fragen. Welt und Wahrheit. Leben und Tod. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Lebensformen, Welt, Gesellschaft. Normen und Werte - Religionen und Kulturen. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Mensch, Natur, Technik. Lebenswelt, Information und Sprache. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne